The perspective of interdisciplinarity in the dissertations of the graduate Program in Professional Education (Research, Society and Development, 2019)
In this article, we analyze the dissertations of the Postgraduate Program in Professional Education - PPGEP / IFRN, belonging to Research Line 2: “Teacher Training and Pedagogical Practices”, defended in 2018. With the objective of analyze and discuss the perspective of the interdisciplinary theme. The research took place through a survey in the Catalog of Theses and Dissertations of the Portal of the Coordination of Improvement of Higher Education - CAPES. As for the results, we found 7 dissertations, of which two did not mention our object of analysis, while the others dialogued with several areas of knowledge, which approach the construction of a more globalized knowledge.